Assessment of ‘Sarva Shiksha Abhiyan’ in Sarvodaya Schools of Delhi - Jain, Sakshi; Mittal, Meenakshi (INDIAN EDUCATIONAL REVIEW, 2011)
The paper examines the effectiveness of Sarva Shiksha Abhiyan (SSA) and focuses on assessing the awareness and satisfaction level of different stakeholders regarding selected programme components. The study revealed that despite some loopholes that were found in the programme, the programme had been very effective in mainstreaming out of school children and reducing dropouts. Some areas that need to be looked into to improve the efficacy of the programme were awareness level about the programme, allocation of funds for teaching-learning material (TLM) and providing NGO’s who are partners in the programme with better funding and timely dispersal of the funds for their smooth functioning.